Dislocation Interactions in Olivine Revealed by HR‐EBSD. Issue 10 (21st October 2017) - Wallis, David; Hansen, Lars N.; Britton, T. Ben; Wilkinson, Angus J.
Abstract: Interactions between dislocations potentially provide a control on strain rates produced by dislocation motion during creep of rocks at high temperatures. However, it has been difficult to establish the dominant types of interactions and their influence on the rheological properties of creeping rocks due to a lack of suitable observational techniques. We apply high‐angular resolution electron backscatter diffraction to map geometrically necessary dislocation (GND) density, elastic strain, and residual stress in experimentally deformed single crystals of olivine. Short‐range interactions are revealed by cross correlation of GND density maps. Spatial correlations between dislocation types indicate that noncollinear interactions may impede motion of proximal dislocations at temperatures of 1000°C and 1200°C. Long‐range interactions are revealed by autocorrelation of GND density maps. These analyses reveal periodic variations in GND density and sign, with characteristic length scales on the order of 1–10 μm. These structures are spatially associated with variations in elastic strain and residual stress on the order of 10 −3 and 100 MPa, respectively. Therefore, short‐range interactions generate local accumulations of dislocations, leading to heterogeneous internal stress fields that influence dislocation motion over longer length scales. The impacts of these short‐ and/or long‐range interactions on dislocation velocities may therefore influence the strain rate of the bulk material and are an important consideration for future models of dislocation‐mediated deformation mechanisms in olivine. Establishing the types and impacts of dislocation interactions that occur across a range of laboratory and natural deformation conditions will help to establish the reliability of extrapolating laboratory‐derived flow laws to real Earth conditions. Key Points: HR‐EBSD map distributions of GND density and elastic stress/strain in experimentally deformed single crystals of olivine Short‐range dislocation interactions impeded glide, resulting in locally elevated GND densities, commonly along slip bands GNDs generate heterogeneous internal stress fields which may influence microstructural organization over micron length scales